Customers’ Trust Transferability in Social Commerce and Its Impact on Perceived Risk and Purchase Intention - Wiyata Wiyata (Indonesian Journal of Social Science Research, 2023)
This study attempts to provide a strengthened understanding of how to mitigate perceived product risk by utilizing the effect of consumers’ trust transfer. Grounding on the theory of perceived risk, trust transfer framework, and social commerce theory, we propose an integrated model of trust-risk perspective on cross-border social commerce use. We tested the proposed model by conducting an online survey in Indonesia. In this work, we used a PLS-SEM analysis, a mediation and a suppression test, and a Multi-Group analysis. The results demonstrated that consumers’ trust can be transferred from the source of trust (platform and friend) to the target of trust (brand), which subsequently reduce perceived product as well as increase purchase intention. More interestingly, the results of the suppression effect testing show that friend trust was able to play a role as a suppressor factor in the relationship between brand trust and perceived product risk. The finding of the present study offers important implications for theory and literature by integrating trust transfer and perceived risk theory and taking into account perceived product risk as an important factor that potentially deters the effect of trust transfer on consumers’ intention to purchase. From a practical implication, we suggest that the best away to gain consumers’ trust in the global market is by conducting an intensive approach to prospective consumers through social media and promoting in popular marketplaces simultaneously.